Integrasi Etnosains Dalam Kurikulum Merdeka Sekolah Dasar Untuk Meningkatkan Keterampilan Berpikir Kritis Dan Problem Solving - Fitria Hidayati; Julianto Julianto (DIDAKTIKA, 2024)
This research aims to examine the role of ethnoscience integration in the independent curriculum in improving students' critical thinking and problem solving skills. The approach used in this research is a qualitative approach by conducting a literature review method. A qualitative approach was chosen because it aims to explore phenomena in depth and understand concepts related to the integration of ethnoscience in the Independent Curriculum and its influence on critical thinking and problem solving skills. The data analysis technique in this research uses descriptive analysis. The research results show that the integration of ethnoscience in the independent curriculum can improve critical thinking and problem solving skills